Frenectomy with laterally displaced flap: A case series - S Janarthanan; R T Arun; S Srinivasan; S Senthil Kumar (Wolters Kluwer Medknow Publications, 2019)
The frenum is a mucous membrane fold that attaches the lip and the cheek to the alveolar mucosa, the gingiva, and the underlying periosteum. The frena may jeopardize the gingival health when they are attached too closely to the gingival margin, either due to an interference in the plaque control or due to a muscle pull. In addition to this, the maxillary frenum may present esthetic problems or compromise the orthodontic result in the midline diastema cases, thus causing a recurrence after the treatment. Archer's "classical frenectomy" is an extensive procedure including the excision of fibers, interdental papilla, and exposure of the alveolar bone up to the palatine papilla. The resultant delayed healing, loss of the interdental papilla, and abnormal scar led toward the conservative approaches such as Edward's frenectomy, frenum relocation by Z-plasty, and free gingival graft, with their technical and esthetic limitations. A better approach in frenectomy to make a primary closure in the midline and to avoid an unesthetic scar by creating a zone of the attached gingiva is assisted with a lateral pedicle graft. A case series of this technique with its distinct advantages is presented.